Timelike asymptotics for global solutions to a scalar quasilinear wave equation satisfying the weak null condition - Dongxiao Yu (Forum of Mathematics, Sigma, 2025)
We study the timelike asymptotics for global solutions to a scalar quasilinear wave equation satisfying the weak null condition. Given a global solution u to the scalar wave equation with sufficiently small